Digital Tourism in the Development of the Arctic Region - BELONOZHKO, Marina L.; BELONOZHKO, Lydia N.; SITEVA, Svetlana S. (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).03, 2019)
The problems considered in the work are determined by modern requirements in the growth of the tourism industry as an important system of social and economic development. Globalization in the tourism sector determines the need to transform and overcome the traditional forms of tourism. Tourism with the actual rhythm of life has ceased to be a means of rest only, it also acts as an active economic agent and a means of maintaining a remote business in its work. This allows us to say that digital tourism can attract a large audience at relatively low cost. The work defines that digital tourism is not only an external manifestation of the possibility of visiting places without detailed specification of their location, but also have access to technologies that allow designing the functioning of tourism facilities taking into account the data received from the introduction of digital technologies. The work shows that digital tourism completely changes the overall structure of the tourism industry, based on stream modeling, which allows tourists to stay in touch and be online during the entire travel period. The schemes of designing such a tourist route are shown, the ways of its introduction into the Arctic tourism sector are revealed, the mathematical model of the design of the capacity of the tourist flow of the Arctic is developed.